THE IMPACT OF E-DEMOCRACY ON TRANSFORMATION OF PUBLIC ADMINISTRATION SYSTEM IN UKRAINE - Нromyko O.I. (Pressing Problems of Public Administration, 2016)
The paper analyzes the state of e-democracy in Ukraine, and correlation between the national systemof public administration and e-democracy principles. Factors that determine the public administrationsystem transformation, influenced bye-democracy development, have been revealed.